A PRAGMATIC APPROACH TO TREAT LUNG CANCER THROUGH LOADING THEAFLAVIN -3,3’-DIGALLATE AND EPIGALLOCATECHIN GALLATE IN SPANLASTIC - IMAM, SYED SAIF; AGARWAL, SMRITI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Lung cancer has the highest mortality rate as compared to other cancers. The anti-proliferative and antioxidant potential of epigallocatechin gallate (EGCG) and Theaflavin -3,3’-digallate (TF3) can play a major role in treatment if delivered efficiently. To improve the chemical stability and medicinal potential of EGCG and TF3 in the respiratory tract, a spanlastic is developed which is composed of Tween-80, Span-60, and cholesterol which encapsulate EGCG and TF3 inside its vesicular structure and deliver it specifically to the target cancer cells. The cholesterol layer will produce efficient penetration while tween-80 and span-60 will help in easily deformability and lowers the interfacial tension hence, produces a small Z-average diameter which facilitates efficient penetration between layers of cells. The nano-vesicular structure ensures the APIs stability at alkaline pH (7.6) and also increases cellular antioxidant activity and Ferric reducing antioxidant powers values of APIs. Better encapsulation efficiency and safe consideration by MTT assay are major advantages of Spanlastic. The lung cancer cell loses the ability of apoptosis, which can revived with the help of a nano-vesicular system of EGCG and TF3 and in addition, there will be activation of several other properties such as cell arrest, activation of miR-210, suppression of cyclin D1, inhibition of MAPK, ERK, and JAK-STAT at their maximum potential. Furthermore, a special type of spacer and pMDI canister are developed in order to maximize the drug stability and efficiency of its delivery.